2018
DOI: 10.18203/issn.2454-2156.intjscirep20185350
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and associated factors among lactating mothers in Debre Tabor General Hospital, Northcentral Ethiopia

Abstract: <p class="abstract"><strong>Background:</strong> Dietary diversity score indicates that the intake of general nutritional adequacy. Low dietary diversity is a major problem among poor populations in the developing world due to consumption of monotonous staple diet consumption. Therefore, it has various consequences on the health and wellbeing of the family, communities, and nation at large. Overall, there are limited studies on this major issue and its contributing factors among lactating mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 13 publications
6
21
4
Order By: Relevance
“…In the present study, mothers who met their minimum meal frequency were six times more likely to meet their MDDS than their counterparts. This is consistent with studies revealed in Ethiopia such as Lay Gayt district ( 17 ) and Debretabor ( 19 ) . The possible reason might be a mother will met the minimum meal frequency if they are from households with food security.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, mothers who met their minimum meal frequency were six times more likely to meet their MDDS than their counterparts. This is consistent with studies revealed in Ethiopia such as Lay Gayt district ( 17 ) and Debretabor ( 19 ) . The possible reason might be a mother will met the minimum meal frequency if they are from households with food security.…”
Section: Discussionsupporting
confidence: 93%
“…The MDDS in the present study is lower than as compared with studies done in other parts of Ethiopia such as Angecha district 47⋅8 % (14) , Dedo and Seqa-Chekorsa district 32⋅8 % (15) , Ataye district 48⋅8 % (16) , Lay Gayt district 34⋅3 % (17) , Dessie town 45⋅5 % (18) , Aksum town 43⋅6 % (9) and Debretabor 75 % (19) showed that lactating mothers met the minimum diet diversity. This finding is also lower than findings from other low-to middle-income countries such as Nepal 53 % (20) and Malawi 28⋅1 % (21) .…”
Section: Discussioncontrasting
confidence: 81%
“…Regarding the meal frequency of pregnant and lactating women in Ethiopia, it was reported by 23 studies (Abriha et al, 2014;Alemayehu & Tesema, 2015;Aliwo et al, 2019;Boke & Geremew, 2018;Kobiro et al, 2020;Demilew et al, 2020;Desalegn et al, 2018;Desta et al, 2019;Diddana, 2019;Duko et al, 2018;Engidaw et al, 2019;Eramo, 2018;Gizahewu et al, 2019;Haileslassie et al, 2013;Hailu & Woldemichael, 2019;Jemal & Awol, 2019;Kumera et al, 2015;Nigatu et al, 2018;Sitotaw et al, 2017;Sonko, 2016;Tikuye et al, 2019;Weldehaweria et al, 2016) with a total of 9,447 study subjects. Of the total study subjects, 7,554 (80%) of pregnant and lactating women ate ≤3 times per day, whereas 1854 (20%) of them ate ≥4 times per day (Table 1).…”
Section: Dietary Practice and Meal Frequencies Of Pregnant And Lactating Women In Ethiopiamentioning
confidence: 99%
“…A total of 18 articles were selected for full article reading and 2 records were additionally removed by the studies were conducted in both lactating and pregnant mothers together [30,31]. Lastly, 16 articles were selected for the nal review and meta-analysis [13,15,16,[32][33][34][35][36][37][38][39][40][41][42][43] [ Figure 1].…”
Section: Study Search and Selectionmentioning
confidence: 99%
“…Ten (62.5%) of the included studies were conducted in 2017 [15,34,36,37,[39][40][41][42][43][44] and then after, and only one of the included studies were conducted before 2010 [32]. Regarding the region where the study conducted 6 (31.2%) were from Oromia [15,33,35,38,39,43], three were from SNNP [34,37,44], three were from Tigray [13,36,40], two were from Amhara [41,42] and 2 were from Addis Ababa [32], and Tigray and Oromia region [16] jointly, one in each. The highest prevalence of undernutrition among lactating women was reported from a study done in Tigray and Oromia region jointly (54.7%) [16] and the least was from the Oromia region (5.6%) [15] [ Table 1].…”
Section: Characteristics Of the Studies And Systematic Reviewmentioning
confidence: 99%